The complex landscape of genetic alterations in mantle cell lymphoma - Royo, Cristina; Salaverria, Itziar; Hartmann, Elena M.; Rosenwald, Andreas; Campo, Elías; Beà, Sílvia (Seminars in cancer biology, 2011)
Mantle cell lymphoma (MCL) is genetically characterized by the t(11;14)(q13;q32) which deregulates cyclin D1. Small subsets of cases have been identified with variant CCND1 translocations with the immunoglobulin light chain genes or with alternative translocations involving CCND2 and CCND3. Additionally, double-hit MCL with MYC rearrangements with a highly aggressive clinical course have been reported, but no other frequent recurrent translocations have been identified. In recent years, genome-wide screening of copy number alterations by comparative genomic hybridization and genomic microarray platforms have revealed a characteristic MCL profile of multiple secondary gains and losses as well as regions of copy number neutral loss of heterozygosity that target mainly genes involved in cell cycle regulation, DNA damage response, and cell survival pathways. Several aberrations have been found to be associated with worse prognosis, 3q gains and losses of 8p, 9p, and 17p. An increased number of secondary alterations and blastoid morphology have also been shown to be associated with cases with short survival. On the contrary, indolent MCL cases carry only the primary t(11;14) and few or no other additional genomic alterations. Altogether these observations suggest that the genetic background of MCL is an important factor that dictates their different clinical behavior. This review will focus on MCL from a genetic perspective and will present next-generation sequencing technology as a new potential tool to complement the study of complex genomes. The better understanding of genetic alterations of MCL may offer new approaches for more patient-tailored, risk-adapted treatment options.